(untitled) (Shanti Journal, 2023)
War is not a destiny, it is a human choice, failure of politics, economics, diplomacy, and security policy. International Relations (IR) is the study of great power relations and how they affect the world. Understanding and conduct of contemporary IR based on old assumptions can be as erroneous and risky as concluding the inevitability of war between two 21st Century great powers based on what scholar Graham Allison reminds us of the "Thucydides’ Trap" , history of two Greek city states which went to war because they could not accommodate each other’s national interests. What is Allison of Harvard’s Kennedy School, arguably one of the greatest global institutions of higher learning and powerhouses of ideas, trying to convey by characterizing 21st Century America-China relations by 5th Century BC Greek city states?